Wafer-scale MoS2 with water-vapor assisted showerhead MOCVD. Issue 20 (22nd September 2022) - Macha, Michal; Ji, Hyun Goo; Tripathi, Mukesh; Zhao, Yanfei; Thakur, Mukeshchand; Zhang, Jing; Kis, Andras; Radenovic, Aleksandra
Abstract : We adapted the most efficient monolayer growth methodologies from tube-furnace systems to the showerhead geometries. A combination of gas-phase precursors, pre-seeding substrate coating and H2 O vapor added during growth yields 4-inch monolayer MoS2 . Abstract : Among numerous thin film synthesis methods, metalorganic chemical vapor deposition performed in a showerhead reactor is the most promising one for broad use in scalable and commercially adaptable two-dimensional material synthesis processes. Adapting the most efficient monolayer growth methodologies from tube-furnace systems to vertical-showerhead geometries allows us to overcome the intrinsic process limitations and improve the overall monolayer yield quality. Here, we demonstrate large-area, monolayer molybdenum disulphide growth by combining gas-phase precursor supply with unique tube-furnace approaches of utilizing sodium molybdate pre-seeding solution spincoated on a substrate along with water vapor added during the growth step. The engineered process yields a high-quality, 4-inch scale monolayer film on sapphire wafers. The monolayer growth coverage, average crystal size and defect density were evaluated using Raman and photoluminescence spectroscopy, X-ray photoelectron spectroscopy, scanning electron microscopy and scanning transmission electron microscopy imaging. Our findings provide a direct step forward toward developing a reproducible and large-scale MoS2 synthesis with commercial showerhead reactors.